Construct Validity and Reliability of The Amsterdam Preoperative Anxiety and Information Scale (APAIS) Indonesian Version - Perdana, Aries; Firdaus, Muhammad Fikry; Kapuangan, Christopher; , Khamelia (Perdatin Pusat, 2015)
Preoperative anxiety has a significant effect on anesthesia and surgery. Currently there is no specific instrument for measuring preoperative anxiety in Indonesian population. APAIS have been used worldwidely to measure preoperative anxiety. APAIS instrument has been used widely to measure preoperative anxiety. The purpose of this study was to obtain the validity and reliability of APAIS instrument in Indonesia. This cross-sectional study enrolled 102 patients in Cipto Mangunkusumo Hospital who underwent elective surgery to answer the Indonesian APAIS one day before operation. The translation utilized backward and upward approach. Following ethic approval, the subjects filled the APAIS instrument one day before the surgery. Construction validity was measured by factor analytic method. The internal consistency was evaluated by Cronbach?s alpha. A total 102 patient (42 men and 60 women) enrolled in this study. Factor analysis showed anxiety scale and similar information in comparison to the original instrument. High reliability Cronbach?s alpha anxiety and need for information scale Indonesian APAIS respectively 0,825 and 0,863. The APAIS scales were independent of sex, previous surgery, type of operation or type of anesthesia. Indonesian APAIS proved to be reliable and valid instrument to measure preoperative anxiety in Indonesian population.